The Routledge Handbook of the Communicative Constitution of Organization - Basque, Joëlle; Bencherki, Nicolas; KUHN, TIMOTHY (Routledge Studies in Communication, Organization, and Organizing, 2022)
This Handbook offers state of the art scholarship on the perspective known as the Communicative Constitution of Organizations (CCO). Offering a unique outlook on how communication accounts for the emergence, change, and continuity of organizations and organizing practices, this Handbook systematically exposes the theoretical and methodological underpinnings of CCO, displays its empirical diversity, and articulates its future trajectory. Placing communication firmly at the centre of the organizational equation, an international team of expert authors covers: The key theoretical inspirations and the main themes of the field The debates that animate the CCO community CCO's methodological approaches How CCO handles classic management themes Practical applications Offering a central statement of CCO's contributions to the fields of organization studies, communication, and management, this Handbook will be of interest to organization studies and communication scholars, faculty, and graduate and advanced undergraduate students, as well as anyone associated with CCO theorizing seeking a comprehensive overview of the theoretical, methodological, and practical tenets of this growing area.